IDNLearn.com provides a comprehensive solution for all your question and answer needs. Our platform provides trustworthy answers to help you make informed decisions quickly and easily.
Sagot :
Answer:
(x-h)^2 + (y-k)^2 = r^2
Step-by-step explanation:
Here, we want to write the standard equation of the circle
We have this as;
(x-h)^2 + (y-k)^2 = r^2
The above equation is the standard equation for the circle
Answer:
(x − 4)2 + (y + 6)2 = 25
(x − 4)2 + (y − (-6))2 = 52
When I compare my equation with the standard form, (x − h)2 + (y − k)2 = r2, I get h = 4, k = -6, and r = 5. The center is at (4, -6), and the length of the radius is 5.
Step-by-step explanation:
edmentum
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is dedicated to providing accurate answers. Thank you for visiting, and see you next time for more solutions.